Development of Integrated Augmented Reality Multimedia in Thermodynamics Material For Physics Learning in Grade XI - Husna, Nadiatul; Nasir, Muhammad; Islami, Nur (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The sophistication of information technology is still not widely utilized and integrated into the learning process in the world of education, even though technology can be one of the driving factors in improving educational progress. This research and development aims to develop mobile learning multimedia integrated with augmented reality on thermodynamic material and determine the level of validity and reliability of the multimedia that will be used to help increase student motivation and concept understanding. AR multimedia was developed using the ADDIE model stages (analysis, design, development, implementation, and evaluation), then validated by experts, namely one media expert lecturer and two teachers who have approximately 10 years of experience in the field of education. Furthermore, a limited trial was conducted on 25 11th grade students of SMA 11 Negeri Pekanbaru. Data were collected using a validation instrument sheet and a response questionnaire sheet. The collected data was analyzed using the Aiken V formula and Pearson product moment correlation. Therefore, if students have difficulty understanding learning concepts, this augmented reality integrated multimedia is highly recommended for use in the learning process